2010
DOI: 10.3109/10409238.2010.502516
|View full text |Cite
|
Sign up to set email alerts
|

The ESCRT complexes

Abstract: The ESCRT machinery consists of the peripheral membrane protein complexes, ESCRT-0, -I, -II, -III, and Vps4-Vta1, and the ALIX homodimer. The ESCRT system is required for degradation of unneeded or dangerous plasma membrane proteins; biogenesis of the lysosome and the yeast vacuole; the budding of most membrane enveloped viruses; the membrane abscission step in cytokinesis; macroautophagy; and several other processes. From their initial discovery in 2001-2002, the literature on ESCRTs has grown exponentially. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
309
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(316 citation statements)
references
References 295 publications
(407 reference statements)
5
309
0
2
Order By: Relevance
“…2B). This showed that various protein complexes are significantly enriched on BMDM phagosomes, including septin 2, 7, 8, 9, and 11, which have recently been shown to be important for phagosome formation 24, several complexes of cytoskeleton proteins associated with ezrin, moesin and Rock2 and Evl 25, proteins of the ESCRT complexes 26, the striatin complex 27 that has not previously been shown to locate to the phagosome, the above‐mentioned integrin complex, and the entire antigen crosspresentation complex associated with Tap2. One would therefore expect considerable differences in the ability to cross‐present antigens via MHC class I between RAW 264.7 cells and BMDMs.…”
mentioning
confidence: 97%
“…2B). This showed that various protein complexes are significantly enriched on BMDM phagosomes, including septin 2, 7, 8, 9, and 11, which have recently been shown to be important for phagosome formation 24, several complexes of cytoskeleton proteins associated with ezrin, moesin and Rock2 and Evl 25, proteins of the ESCRT complexes 26, the striatin complex 27 that has not previously been shown to locate to the phagosome, the above‐mentioned integrin complex, and the entire antigen crosspresentation complex associated with Tap2. One would therefore expect considerable differences in the ability to cross‐present antigens via MHC class I between RAW 264.7 cells and BMDMs.…”
mentioning
confidence: 97%
“…In immature DCs, surface expression of a K225 mutant of MHCII b was dramatically increased in comparison to wild-type MHCII b (Shin et al 2006;van Niel et al 2006;Matsuki et al 2007), with the major cause being that sorting at MVBs into ILVs was .20-fold less efficient (van Niel et al 2006). Ubiquitination-driven cargo sorting and ILV formation at endosomes are facilitated by the endosomal sorting complex required for transport (ESCRT) (Raiborg and Stenmark 2009;Hurley 2010;Henne et al 2011Henne et al , 2013Piper et al 2013). Consistent with its generic role, it can be expected that the ESCRTmachinery also drives sorting of ubiquitinated MHCII into ILVs.…”
Section: Sorting Of Mhcii At Mvbsmentioning
confidence: 99%
“…GTP hydrolysis then produces conformational changes that result in fission (Ferguson and De Camilli 2012). In contrast, the ESCRT-III complex appears to assemble on the inside or at one of the openings of the neck to induce membrane constriction and, ultimately, fission (Hurley 2010;Henne et al 2011). The ESCRT-III complex has been implicated in the biogenesis of multivesicular bodies (Gruenberg and Stenmark 2004;Hurley 2008;Wollert et al 2009;Wollert and Hurley 2010), membrane abscission during cytokinesis (Elia et al 2011), and budding of some enveloped viruses from the host membrane (Strack et al 2003;Morita and Sundquist 2004;Bieniasz 2006).…”
mentioning
confidence: 99%
“…In enveloped viruses, membrane fusion proteins that are anchored in the viral membrane insert into host cell membranes and, through a series of conformational changes, bring the lipid bilayers into close proximity, leading to fusion. As for fission, the only factors described to date that participate in it are dynamin (Ferguson and De Camilli 2012) and the endosomal sorting complex required for transport (ESCRT-III complex) (Hurley 2010;Wollert and Hurley 2010;Henne et al 2011). Dynamin and dynamin-like proteins are involved in endocytosis, multivesicular membrane budding, cytokinesis in chloroplasts, and mitochondrial genesis.…”
mentioning
confidence: 99%